Mechanisms of butylidenephthalide for twitch facilitation in electrically stimulated mouse vas deferens - Chung-Hung Shih; Chi-Ming Chen; Wun-Chang Ko (Taylor & Francis Group, 2018)
Context: The rhizome of Ligusticum chuaxiong Hort. (Umbelliferae) has been used by Chinese for several thousand years. Its main constituent, butylidenephthalide (Bdph), was proved to be active in inhibiting rat uterine contractions induced by prostaglandin F2α and was reported to be a nonspecific antispamodic and a blocker of voltage-dependent Ca2+ channels (VDCCs). Objectives: The present study investigates the mechanisms of Bdph for twitch facilitation in ICR mouse vas deferens (MVD). Materials and methods: Electrical field stimulation (EFS, supramaximal voltage ranging from 60-90 V, 1 ms, 0.2 Hz) was applied to the isolated MVD in Krebs solution. Interactions between Bdph (50 µM) and calcium antagonist (verapamil, diltiazem or aspaminol) on the EFS-evoked twitch responses were determined. The number of experiments was 3-18. Results: Bdph (50 µM)-induced twitch facilitations from 100 to 391.9% were unrelated to activation of postjunctional cholinergic or adrenergic receptors. Verapamil and Bdph unabolished the twitch facilitation each other. Diltiazem unabolished the Bdph-induced twitch facilitation. In contrast, Bdph abolished those induced by diltiazem. Aspaminol at 20 μM abolished the Bdph-induced twitch facilitation. In contrast, Bdph abolished those induced by aspaminol. Tetraethylammonium and 4-aminopyridine, the K+ channel blockers, significantly augmented the Bdph-induced twitch facilitation. Discussion and conclusions: Bdph may bind to the different, more and same subtypes of VDCCs from verapamil, than diltiazem, and as aspaminol does on prejunctional membrane, respectively. Besides a blocker of VDCCs, Bdph may be a blocker of K+ channels on prejunctional membrane. Thus, Bdph depolarized the membrane and facilitated the cumulative Ca2+-induced twitch responses.